Single oral dose of maraviroc does not prevent ex-vivo HIV infection of rectal mucosa in HIV-1 negative human volunteers. (23rd October 2015) - Coll, Josep; Moltó, José; Boix, Jaume; Gómez-Mora, Elisabet; Else, Laura; García, Elisabet; Paredes, Roger; Ouchi, Dan; Carrillo, Antonio; Escrig, Roser; Back, David; Clotet, Bonaventura; et al.
Abstract : Objective: Maraviroc (MVC) is a potential candidate for 'on demand' preexposure prophylaxis. In the present study, we evaluated the efficacy of a single oral dose of MVC to prevent ex-vivo HIV-1 infection of rectal tissue in humans. Design and Methods: Eight HIV-1-negative healthy volunteers received a single oral dose of MVC (300 or 600 mg), and two additional volunteers received tenofovir disoproxil fumarate/emtricitabine (TDF/FTC, 300/200 mg) for 10 days. Rectal biopsies were performed prior to the ex-vivo challenge (day 0), at day 7 (4 h after MVC) or after 10 days with TDF/FTC. Rectal biopsies were infected ex-vivo, and viral inhibition and CCR5 occupancy was analyzed. MVC concentration in plasma and rectal tissue was measured just after biopsy and after viral incubation. Results: Ex-vivo rectal tissue protection with MVC was incomplete in all but two participants, whereas TDF/FTC avoided ex-vivo infection in the two controls. Median dose-normalized concentration of MVC was significantly higher in rectal tissue than in plasma (561.1 and 155.1 ng/ml, respectively). A significant loss of MVC during the virus incubation (about 60%) and a low CCR5 occupancy (approximately 45%) were detected in rectal cells. Conclusions: An ex-vivo challenge with a single oral dose of MVC does not prevent ex-vivo infection of human rectal mucosa. The lack of prophylactic efficacy observed suggests that 'on demand' MVC preexposure prophylaxis would not prevent rectal HIV-1 transmission.